Peningkatan Keterampilan Membaca Intensif melalui Metode Pembelajaran Kooperatif Tipe STAD Siswa Kelas XI IPS 3 MAN I Pekanbaru - Zulmi Zulmi (Milenial: Journal for Teachers and Learning, 2022)
This research is to explain the process of increasing intensive reading skill on students class XI social 3 MAN 1 Pekanbaru thought STAD cooperative study method. The subject of the research is the student’s class XI social 3 MAN 1 Pekanbaru which is consist of 24 students. The subject is chosen because based on the observation the class has the lowest achievement compare with another classes. The data is taken in form of qualitative and quantitative. Qualitative data is collected by onservation, picture and videos. Quantitative data is taken fromstudent’s achievement and student’s observation sheet. The finding of the research suggestthat the using of STAD cooperative study method can increase student’s intensive reading skill in determine the fact and opinion sentence and utter the head line of a text. Based on the findings, the writer conclude that: (1) The using of STAD cooperative study method in determining fact and opinion sentence can increase the student’s achievement on class XI social 3 MAN 1 Pekanbaru. (2) The factors to increase it are: a) teacher attitude in the process of intensive reading study. b) The good communication between teacher and student’s, student’s and student’s among them selves. c) The right study method used by the teacher in intensive teaching process. And d) The fun and happy condition of teaching createdby the teacher